The effects of perceived cultural conflicts on employee retention after mergers and acquisitions - LUAN, Chengpeng (Institutional Knowledge at Singapore Management University, 2024)
With China’s deepening medical reform, the state has introduced a series of regulatory policies, which has set off a frenzy of mergers and acquisitions in the medical device industry. Small and medium-sized device distribution companies with small scale and weak strength have closed. Large and powerful large medical device distribution enterprises seize the opportunity to expand mergers and acquisitions rapidly. Based on the researcher's work experience and data availability, this paper takes an MNC company, M, acquisition of a high-quality local company, K, as the research object. Based on the actual operation of the medical device industry, combined with the cultural characteristics of state-owned and private enterprises, the focus of cultural conflicts during the merger and purchase of private businesses by MNCs is the subject of this essay. Investigate methods for implementing cultural integration following the merger and purchase of medical equipment companies. First, this essay provides a succinct overview of the two sides of the merger and acquisition debate, briefly describes the merger process and the generation of culture conflict phenomenon after the completion of the merger by classifying the conflict phenomenon to do variable design and preliminary questionnaire, and then do preliminary screening and testing of the collected questionnaires to form the final questionnaire, and then use SPSS 3.0 to analyze the collected questionnaire data. The influence of four aspects of cultural conflict on the intensity of conflict was studied. Through the data analysis, the focus culture conflict of M company's merger and acquisition of company K mainly focuses on the behavioral culture conflict. However, according to the cultural structure and mutual relationship, it can be seen that the behavioral culture conflict is inevitably behind the impact of institutional culture conflict and spiritual culture conflict. After mergers, different cultural conflict factors have varying degrees of impact on talent retention. The cultural conflict factors affect the retention of talent in various positions. Based on the results of the survey, we can see the following findings: a.The years of service within the acquired company significantly influence turnover after the merger. Employees working longer in the acquired company are more inclined to leave after the merger. b.There are significant differences in the turnover rates among employees in different positions. e.g., sales position. c.After the merger, employees consider the opportunity for self-improvement in the company as a factor influencing turnover. The greater the perceived opportunity for self-improvement, the more likely employees will remain after the merger. d.Employees consider the adequacy of the company's talent development mechanisms as a factor influencing turnover. The higher the evaluation of the development mechanisms, the more likely employees are to remain after the merger. The innovation of this paper starts with the actual operation of MNC and domestic medical device enterprises, giving full consideration to the cultural characteristics between them. Secondly, cultural conflict and integration are ubiquitous in mergers and acquisitions but cannot be seen and touched. Third, talent retention is one of the critical determinants of post-M&As integration success. This paper uses the quantitative method to make up for the shortcomings of the existing qualitative analysis.